For What It’s Worth: Power of Symbols and Symbols of Power - Coulmas, Florian (Recherches sémiotiques / Semiotic Inquiry, 2021)
This short essay discusses a particular relationship between language and money. On the face of it (at face value?) the two are rather different; however, closer inspection shows them to have a number of similar properties, such as relying on mutual trust and being subject to a political regime. Accordingly, they also serve similar functions, which are explored here. The economy of language provides a framework for studying similarities and differences of these means of exchange. Particular attention is given to the power of language and the power of money.